2012
DOI: 10.1097/hjh.0b013e328359562c
|View full text |Cite
|
Sign up to set email alerts
|

Reference values of aortic pulse wave velocity in a large healthy population aged between 3 and 18 years

Abstract: Objective. The measurement of aortic pulse wave velocity (PWV ao

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
4
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 34 publications
4
66
4
3
Order By: Relevance
“…An association between PWV and age was previously demonstrated in a large group of children. 24 Despite the positive correlation between PWV and BMI observed in our sample (Table 4), the latter did not prove to be a significant predictor of PWV on regression analysis. Other authors have documented associations between PWV and other markers of cardiovascular risk such as preperitoneal fat tissue thickness and waist/hip circumference.…”
Section: Discussioncontrasting
confidence: 60%
“…An association between PWV and age was previously demonstrated in a large group of children. 24 Despite the positive correlation between PWV and BMI observed in our sample (Table 4), the latter did not prove to be a significant predictor of PWV on regression analysis. Other authors have documented associations between PWV and other markers of cardiovascular risk such as preperitoneal fat tissue thickness and waist/hip circumference.…”
Section: Discussioncontrasting
confidence: 60%
“…In the general adult population, PWV increases with increasing age and blood pressure levels. 41 However, in children, the influence of age on PWV is less clear [42][43][44] and may be confounded by pubertal status. One study in a healthy population of children between the ages of 3 to 18 years, reported that PWV remained unchanged during childhood but started to increase in girls at 10.4 years and in boys at 12.1 year, 42 suggesting an influence of pubertal status rather than age.…”
Section: Discussionmentioning
confidence: 99%
“…41 However, in children, the influence of age on PWV is less clear [42][43][44] and may be confounded by pubertal status. One study in a healthy population of children between the ages of 3 to 18 years, reported that PWV remained unchanged during childhood but started to increase in girls at 10.4 years and in boys at 12.1 year, 42 suggesting an influence of pubertal status rather than age. 45 Sex and pubertal status, through changes in vasoactive hormone concentrations, are critical factors known to influence arterial wall properties and function.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, the ‘gold standard' for the noninvasive assessment of arterial stiffness is carotid-femoral PWV (cfPWV) [5]. While other methods of assessing aortic PWV have been validated, and largely show comparable results [7,8,9], in this paper, we will primarily focus on cfPWV as measured by applanation tonometry, unless otherwise specified.…”
Section: How To Measure Arterial Stiffness?mentioning
confidence: 99%